IDENTIFIKASI PARASIT YANG MENGINFEKSI BENIH IKAN KERAPU MACAN (Epinephelus fuscoguttatus) DI KERAMBA JARING APUNG (KJA) - Fiki Harjuni; Yoppie Wulanda; Herman Sarumaha; Farhan Ramdhani; Lauura Hermala Yunita; Muhammad Latiful Khobir (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2023)
Diseases and pest outbreaks in fish have until now become the main obstacle factors in increasing aquaculture production, both intensively and extensively. Fish disease causes huge economic losses for the community, especially farmers, one of the commodities is tiger grouper (Ephinepehelus fuscoguttatus). Some obstacles in grouper farming include the high mortality rate. Disease is an inhibiting factor in grouper farming. The purpose of this study was to examine what parasites infect tiger grouper (Ephinepehelus fuscoguttatus). This research was conducted in the Floating Net Cage (KJA) of Tapian Nauli I Village, Central Tapanuli Regency in November 2022 using the survey method. Then direct observation of parasites at the Fish Health Laboratory of the College of Fisheries and Marine Matauli. The results of parasite examination on tiger grouper (Ephinepehelus fuscoguttatus) in Floating Net Cages (KJA) in Tapian Nauli I Village Waters, Central Tapanuli Regency were the discovery of parasites of Diplectanum sp, Haliotrema sp, parasite eggs, Benedenia sp, Vorticella sp, and Attheyella sp.